The Effect of Teaching through Case Study Method of the Acquisition of Learning Outcomes and Retention of the Learning in the Course of Citizenship and Democracy Education - Cakmak, Zafer; Akgun, Ismail Hakan (Pamukkale Univ, 2016)
The purpose of this study; is to determine the level and retention by the case study method of learning in the Course of 8th Grade Citizenship and Democracy Education. This research was designed pre-test-posttest study, an experimental and a control group experimental model. In the experimental group with case study method of teaching, control group education program was carried out as prescribed. Before and after the program to students in the academic achievement test was applied as pre-test and post-test, post-test 56 days after the implementation of the retention test was given to the group. There suiting data analysis, t-test is made by the results obtained are as follows: The teaching process at the end of the experimental and control groups applied to the post-test and retention test results according to the experimental group students' academic achievement in the control group of students was significantly higher respectively.
Keywords: Case StudyMethod; DemocracyandEducation; CitizenshipandEducation; CitizenshipandDemocracyEducation